The Role of Diffusion-Weighted Imaging in the Evaluation of the Whole Brain in Isolated Unilateral Polymicrogyria. (December 2016) - Görkem, Sureyya Burcu; Doganay, Selim; Gumus, Kazim; Bayram, Ayse; Kumandas, Sefer; Coskun, Abdulhakim
The aim is to evaluate normal-appearing brain regions in isolated unilateral polymicrogyria patients and compare them with controls by using diffusion-weighted imaging and apparent diffusion coefficient. The diffusion-weighted images ( b = 0-1000 s/mm 2 ) of 10 pediatric patients (7 boys, 3 girls; mean age = 5.8 ± 4.3 years) with isolated unilateral polymicrogyria and age-sex matched 10 control patients were assessed retrospectively. There was a significant increase in apparent diffusion coefficient values of white matter underlying polymicrogyria, uninvolved white matter, deep gray matter (thalami, lentiform nuclei, caudate nuclei) and corpus callosum in polymicrogyria patients compared to control group ( P < .01). The whole brain might be affected in isolated unilateral polymicrogyria patients. The abnormal deep gray matter in polymicrogyria patients would indicate a new point of view for pediatric neurologists about the probability of additional future neurological disorders.